Laboratory Study On The Utilization of Jackruit Skin Waste Into Car-boxymethyl Cellulose and Their Effect On The Rheological Properties Of Drilling Mud - Novrianti Novrianti; Adi Novriansyah; Idham Khalid; Zata Dini Amani (UIR PRESS, 2022)
The value rheology of drilling mud must be in accordance with the conditions of wellbore that do not lead to the occurrence of the problems at the time of drilling. One of the efforts to improve the rheology of drilling mud is by adding Carboxymethyl Cellulose (CMC) which is useful for increasing viscosity and binding water. This study aims to identify the effect on the use of CMC originating from jackfruit skin to the rheological properties of drilling mud. Jackfruit skin is an underutilized organic waste and the structure of jackfruit skin contains 50-55% cellulose. Manufacturing phase of synthesizing CMC skin jackfruit includes the process of delignification, alkalization, carboximetilation, and sieve sample to be powdered CMC and subsequently carried out the test of plastic viscosity, yield point , gel strength by using a Fann VG Meter and mud cake using a marsh funnel and volume filtration using a filter press . The added mass of CMC jackfruit skin were varied from 1 g, 2 g, 3 g, 4 g to 5 g. The results suggest that the addition of jackfruit skin CMC has an effect on the rheology of drilling mud. Increasingly many additions additive CMC skin jackfruit who use the increasingly high- value rheology mud drilling were obtained. Furthermore, the addition of CMC jackfruit skin starting from 1gr – 5 gr meets the API 13, a standard for the value of yield point/viscosity plastic, plastic viscosity and maximum volume of filtrate. While the value of gel strength which meets the API 13 A is with the addition of CMC jackfruit skin as much as 5 grams.